Data-based Reconstruction of Gene Regulatory Networks of Fungal Pathogens - Guthke, Reinhard; Gerber, Silvia; Conrad, Theresia; Vlaic, Sebastian; Durmuş, Saliha; Çakır, Tunahan; Sevilgen, F. E.; Shelest, Ekaterina; Linde, Jörg (Frontiers in Microbiology, 2016)
In the emerging field of systems biology of fungal infection, one of the central roles belongs to the modelling of gene regulatory networks (GRNs). Utilising omics-data, GRNs can be predicted by mathematical modelling. Here, we review current advances of data-based reconstruction of both small-scale and large-scale GRNs for human pathogenic fungi. The advantage of large-scale genome-wide modelling is the possibility to predict central (hub) genes and thereby indicate potential biomarkers and drug targets. In contrast, small-scale GRN models provide hypotheses on the mode of gene regulatory interactions, which have to be validated experimentally. Due to the lack of sufficient quantity and quality of both experimental data and prior knowledge about regulator–target gene relations, the genome-wide modelling still remains problematic for fungal pathogens. While a first genome-wide GRN model has already been published for Candida albicans, the feasibility of such modelling for Aspergillus fumigatus is evaluated in the present article. Based on this evaluation, opinions are drawn on future directions of GRN modelling of fungal pathogens. The crucial point of genome-wide GRN modelling is the experimental evidence, both used for inferring the networks (omics ‘first-hand’ data as well as literature data used as prior knowledge) and for validation and evaluation of the inferred network models.